Advances in Smart System Technologies Select Proceedings of ICFSST 2019 - Suresh, P.; Saravanakumar, U.; Hussein Al Salameh, Mohammed Saleh; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book presents select peer-reviewed proceedings of the International Conference on Frontiers in Smart Systems Technologies (ICFSST 2019). It focuses on latest research and cutting-edge technologies in smart systems and intelligent autonomous systems with advanced functionality. Comprising topics related to diverse aspects of smart technologies such as high security, reliability, miniaturization, energy consumption, and intelligent data processing, the book contains contributions from academics as well as industry. Given the range of the topics covered, this book will prove useful for students, researchers, and professionals alike.
1. Smart systems -- 2. Intelligent and automation -- 3. Communication systems and networking -- 4. Computing and computer systems.
Keywords: Computational intelligence; Wireless communication systems; Mobile communication systems; Robotics; Automation; Signal processing; Image processing; Speech processing systems; Electronic circuits; Computational Intelligence; Wireless and Mobile Communication; Robotics and Automation; Signal, Image and Speech Processing; Circuits and Systems